A Flexible Payment Scheme in Hotel Business - DONG, Ciwei (Institutional Knowledge at Singapore Management University, 2010)
This paper introduces a flexible payment scheme in the hotel business. When a customer makes a reservation for a hotel room, the hotel offers an optional payment scheme (Scheme O). If the customer chooses the Scheme O, he/she makes a non-refundable down payment immediately. Meanwhile, the hotel offers a discount if the customer actually checks in to the hotel. Thus, the payment at check-out time is much lower than the original rental rate. Alternatively, if the customer rejects the Scheme O, the reservation is made under a traditional Scheme (Scheme T), where no down payment is required. However, the customer choosing Scheme T must make a full payment without any discount when he checks out from the hotel. The value of Scheme O depends on customers' cancelation or no-show due to the competition from nearby hotels. We consider two scenarios: 1). the hotel knows the expected value of competitor's rental rate (deterministic case); 2). the hotel knows the stochastic distribution of competitor's rental rate (stochastic case). We have obtained optimal solutions for Scheme O for both deterministic and stochastic cases. Moreover, we also study the interaction between designing a flexible payment scheme and pricing on the rental rate of hotel room.